Up/down impurity density asymmetries in C-Mod plasmas. (20th September 2018) - Rice, J.E.; Reinke, M.L.; Cao, N.; Hughes, J.W.; Ashbourn, J.M.A.; Ernst, D.R.; Hubbard, A.E.; Irby, J.H.
Abstract: Brightness profiles of x-ray emission from H-like Ar 17+ exhibit a distinct up/down asymmetry under certain operating conditions in C-Mod plasmas, indicating that impurity densities are not constant on flux surfaces with r / a between  ̃0.8 and  ̃0.95. In L- and I-mode plasmas, there is an x-ray brightness excess, up to a factor of 8, on the side opposite to the ionB   ×   B drift direction. This effect is not observed in H-mode plasmas, presumably due to edge impurity transport being dominated by a strong inward pinch, which is absent in L- and I-mode. The magnitude of the asymmetry in L- and I-mode decreases with increasing plasma current, similar to the observed decrease in radial impurity diffusivity. In I-mode, where the codependence between electron density and temperature can be broken with ICRF heating power, the asymmetry magnitude is found to decrease with increasing density and with increasing edge temperature at fixed density. These measurements exhibit some qualitative features of neo-classical expectations but the observed asymmetry magnitude is much larger than predicted and some scalings with plasma parameters are not seen. The up/down asymmetry appears to be largest when the cross field impurity diffusivity is the highest.